EL METROPOLITANO: ¿EN VÍAS DE SER UN MONOPOLIO? - Herrera García, Beatriz (2012)
Currently, in our capital, problems arise related to transportation, as excess traffic, the negligence of drivers, poor service provided and the lack of respect to the user of these public service companies. It has long been wanted to find the solution to improve the road system Lima, then arise the option of THE METROPOLITAN, according to its creators, a modern system, faster, practical, that would change our vial culture. Thus begins its construction and implementation, and will be expected to establish an order and improve the public transport system, but arose problems that bothered to much of the population near of its routes, because of municipal regulations, since many routes that attended to several users, were diverted. It imposed to the population a single option: use only The Metropolitan. Certainly, people who already had a custom were affected by being forced to use it as their only road vial. In addition, complaints arose about the high cost of service. In this paper, we analyze the characteristics of the market that has been affected by the implementation of the Metropolitan and determine whether the system is on track to become a monopoly.